Implikasi Ambiguitas Pemaknaan “Lembaga Pemerintah Lainnya” dalam Undang-Undang Kementerian Negara Terhadap Batas Kewenangan Presiden - Wibisena Caesario (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
The phrase “other government institutions” in Article 25 of Law No. 61 of 2024, which amends Law No. 39 of 2008 concerning State Ministries, creates interpretative ambiguity due to the absence of a definition or delineation of the institutions referred to. At the same time, Article 25 of Law No. 61 of 2024 grants broader authority to the President compared to its predecessor. Therefore, it is important to examine the implications of this ambiguity for the expansion of presidential powers as formulated in Article 25. This study raises two research questions: (1) What are the possible interpretations of the phrase “other government institutions” under Law No. 61 of 2024? (2) What are the implications of such interpretative ambiguity for the limits of presidential authority? This normative legal research employs a descriptive analytical method. The study identifies several potential interpretations of the ambiguous phrase and reveals two key expansions of presidential authority influenced by it: (1) the broadening of presidential power to regulate the structure and responsibilities of government institutions across sectors and/or administrative levels; and (2) the opportunity for the President to establish and/or govern new types of institutions distinct from Ministries, Non-Ministerial Government Institutions (LPNK), and Non-Structural Institutions (LNS).